Education for Young Women Regarding the Relationship between Knowledge, Attitudes, Nutritional Status and Eating Frequency to Anemia - Al-Bahra; Fathiyati (Unit Penelitian dan Pengabdian Masyarakat STIKES Fatmawati Jakarta, 2023)
Anemia due to iron (Fe) deficiency is a major nutritional problem in Asia, including in Indonesia. Reports from various studies in Indonesia show that the prevalence of nutritional anemia in young women is still high, ranging from 20-50%. The purpose of this study was to provide education to young women regarding the relationship between knowledge, attitudes, nutritional status and eating frequency with anemia. This research is an analytic survey type with a cross sectional design. The population in this study were all Fatmawati STIKes female students, totaling 414 people. Samples were taken as many as 126 respondents, the sampling technique with Proportional Random Sampling. Data collection was carried out with primary data using a questionnaire. Data analysis with univariate, bivariate, multivariate. The results of the study showed that 38.9% of respondents experienced anemia. The results of univariate analysis obtained high knowledge (81.0%), positive attitude (50.8%), normal nutritional status (BMI 18.5 - <25.0) of 81.7% and frequency of eating ≥3 times/day ( 55.6%). The results of the bivariate analysis showed that there were four related variables, namely knowledge (p=0.016; OR=3.333), attitude (p=0.049; OR=2.220), nutritional status (p=0.031; OR=3.022), eating frequency (p=0.000; OR=35,282). The results of the multivariate analysis showed that the factors associated with anemia in female adolescents were eating frequency (p=0.000; OR=38.479) while knowledge was the confounding variable. The dominant factor associated with anemia in female adolescents is eating frequency. Eating frequency is a variable associated with anemia in female adolescents. It is suggested to Fatmawati STIKes students to increase the frequency of regular meals 3 times/day with a balanced nutritional menu that is high in iron (Fe).